On the Issue in Classification of Financial Control Types - I. G. Lvova (Сибирское юридическое обозрение, 2014)
The article is devoted to the issues in classification types (forms) of financial supervision, in order to regulate legal budget relationship. The author analyzes the existing in scientific literature approaches to the concept and content of internal and external controls.